Brief integrative Adlerian couples therapy - Microtraining Associates ([Framingham, MA.] : Distributed by Microtraining Associates, 2003)
In this video, Jon Carlson demonstrates the use of Adlerian therapy to help a couple struggling with issues of anger and temper control. He explains how to draw out the couple's stories and strengths using such strategies as early recollections, pattern recognition, and psychoeducation
Title from title screen
Therapist: Jon Carlson
Keywords: Marital psychotherapy; Adlerian psychology